EFL Vietnamese Students towards Language Learning Autonomy - Phan Thi Kim Thao (Universitas Muhammadiyah Prof. DR. HAMKA, 2018)
Language autonomy is one of aspects in second language acquisition. It becomes vital theme for many scholars and researchers to investigate how language learners take responsibility for their study. The current paper attempts to examine language autonomy strategies were used EFL Vietnamese students to engage the language process as well as EFL teachers’ perceptions towards students’ language learning autonomy. The study used mixed research method. There were 246 participants consisting of 238 English major students and 8 EFL teachers were surveyed by questionnaire and semi-structured interview to indicate their own perceptions on language learning autonomy. The result showed high percentage of learners are independent in learning and EFL teachers’ perceptions on students’ language learning. Keywords: Learning strategy, language autonomy, EFL students.